PENGARUH MODEL JIGSAW TERHADAP HASIL BELAJAR PKN SISWA KELAS V SDN PONTIANAK BARAT - Arief Gunawan; Tahmid Sabri; Suhardi Marli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research  was to analyze the influence of the Jigsaw learning model on the learning outcomes of Civic Education of fifth grade students of West Pontianak 13th Elementary School. The methode of this reseach was an experiment, a form of Quasi Experimental type of non equivalent group design. The research population was all fifth grade students of West Pontianak Elementary School 13 with the number of students were 72 students. The sampling technique uses purposive sampling. The technique used is direct observation and measurement. Data collection tools in the form of observation sheets and multiple choice tests. The results of data analysis are, the average score of the control class post-test is 62,095 and the experiment is 68,786. Based on the results of the t-test calculation obtained by tcount 3,036 > ttabel 1,980, then Ha is accepted. This shows that there is an influence on student learning outcomes by applying the Role Playing method. Calculation of effect size is 0,72 with high criteria. The conclusion of this research that there is the influence of the Role Playing learning method on the learning outcomes of Civic Education in fifth grade students of West Pontianak 13 Elementary School in the high category.Keywords: Learning model for Jigsaw, Learning Outcomes, Civic Education